Code Switching in Indonesian Idol 2012 Program: A Case Study of the Judges’ Comments and the Viewers’ Attitudes - Andita Pribana Dewi (Passage, 2013)
The study entitled “Code Switching in Indonesian Idol 2012 Program: A Case Study of the Judges’ Comments and the Viewers’ Attitudes” aims to investigate the types and functions of code switching and the viewers’ attitude to the use of code switching. Transcripts of 23 videos and interviews of 10 viewers of University students were used as data. Some main theories were used to analyse the data, namely Poplack (1980), Koziol (2000), and Garrett (2010). Based on the results of analysis, this study shows that all types of code switching were found in Indonesian Idol 2012 program judges’ comments namely intrasentential switching, intersentential switching, and tag switching. Ten functions were identified such as emphasis, untranslatability, mitigating message, reiteration, clarification, aggravating message, quotation, personalization, designation, and interjection. In addition, the results also reveal that the viewers mostly show their positive attitudes as they take code switching phenomena as the media for learning a language.Keyword: Code Switching, Types of Code Switching, Functions of Code Switching, Attitudes